Determination of Optimal Temperature and pH for Radial Growth of Some Dermatophyte Species Isolated from Leukemia Patients - M. Hasan, Alaa; H. AL-Jubori, Muna (Iraqi Journal of Science, 2023)
Determination of Optimal Temperature and pH for Radial Growth of SomeDermatophyte Species Isolated from Leukemia Patients